IMPLEMENTASI BIAH LUGHOWIYYAH UNTUK MENINGKATKAN KETERAMPILAN MENDENGAR DAN BERBICARA BAHASA ARAB DI SEKOLAH TINGGI ILMU BAHASA ARAB (STIBA) AR-RAAYAH SUKABUMI - Asep Ahmad Saepudin, - (2021)
Applying Linguistic Environment to Develop Listening and Speaking Skills at STIBA Ar-Raayah (A Descriptive Study on the First Semester Students of I'dad Lughawiy Department) Educational institution that applies linguistic environment has increased in number, but some of them do not clarify their position towards teaching the skills of listening and speaking. Likewise, studies on the subject of linguistic environment did not come out with a comprehensive applied concept of linguistic environment and with a detailed method of applying it to develop listening and speaking skills. This study aimed to know the position of STIBA Ar-Raayah towards the teaching of listening and speaking skills, its point of view in the linguistic environment, describing its application to develop listening and speaking skills, and revealing the obstacles related to them. To achieve these goals, the researcher used descriptive approach based on the three methods of data collection, namely: observation, interview, and documentation. The data were analyzed by the descriptive analysis method. The study resulted in the following: 1) The clarity of STIBA Ar-Raayah's position towards teaching the skills of listening and speaking through its efforts since it was established. 2) Successful linguistic environment was built according to the basic elements, which are; the clarification of the vision, mission and goals in teaching Arabic, the presence of strong systems, human resources whose idea and interaction were united, the presence of places where the systems and means available therein, the establishment of the necessary official study, and the preparation of supplementary programs. 3) The application of linguistic environment at STIBA Ar-Raayah ran according to the concept taken by the university and helped to develop listening and speaking skills. 4) Obstacles in applying linguistic environment for the development of listening and speaking skills were due to three aspects, namely: aspect of human resources represented by the students, non-teaching and administrative staff, aspect of places, and aspect of activities. The researcher recommends a study on applying linguistic environment to develop reading and writing skills. Penelitian ini didasari dengan adanya isu tentang biah lughowiyyah yang diterapkan di beberapa lembaga pendidikan yang tidak efektif. Peneliti melihat bahwa lembaga tersebut belum memfokuskan diri untuk pengajaran Bahasa Arab. Selain itu, studi tentang Biah Lughowiyyah sudah banyak diteliti, namun peneliti belum mendapatkan konsep yang utuh tentang Biah Lughowiyyah dan penerapannya secara mendatail. Maka, peneliti melihat STIBA Ar Raayah untuk mengungkap konsep Biah Lughowiyyah yang dijadikan sandaran dan bagaimana penerapannya, serta kendala yang didapati dalam penerapannya. Peneliti menggunakan pendekatan kualitatif deskriptif dalam mencapai tujuan-tujuan tersebut dan mengumpulkan data-data dengan cara observasi, wawancara, dan dokumentasi. Kemudian menganalisisnya sesuai langkah analisis data deskriptif. Penelitian ini menghasilkan beberapa poin penting, diantaranya: 1) Posisi STIBA Ar Raayah sebagai lembaga pengajaran Bahasa Arab terbukti dan jelas, 2) Konsep Biah Lughowiyyah yang ideal menurut STIBA Ar Raayah terbentuk dengan adanya unsur-unsur berikut: pertama, keterpaduan visi, misi, dan tujuan lembaga pendidikan yang mengarah kepada pendidikan bahasa Arab. Kedua, adanya peraturan tertulis yang mengikat, diterapkan terhadap seluruh warga masyarakat di lingkungan lembaga pendidikan. Ketiga, seluruh tempat/area adalah Biah Lughowiyyah. Keempat, sikap positif dan kerjasama yang baik dari seluruh masyarakat di dalam lembaga tersebut terutama seluruh gruru dan pembina. Kelima, penyelenggaraan pembelajaran wajib. Keenam, adanya kegiatan pendukung di luar kelas. 3) Implementasi Biah Lughowiyyah di STIBA Ar Raayah dilaksanakan sesuai dengan konsep yang dianutnya. 4) Ada beberapa kendala dalam penerapan Biah Lughowiyyah di STIBA Ar Raayah yang berasal dari mahasiswa, pegawai selain dosen dan TU, serta beberapa area yang rentan terhadap pelanggaran Bahasa. Peneliti merekomendasikan peneliti lain untuk mengungkap penerapan Biah Lughowiyyah dalam meningkatkan keterampilan membaca dan menulis.